Second-order phase transitions in crystalline media under the temperature effects - Borts, B.V.; Skoromnaya, S.F.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2022)
Various approaches to describe phase transitions in crystalline media are considered: Landau phenomenological approach of second-order phase transitions as well as Kolmogorov’s, Avrami’s and Christian’s theories of crystallization. An analysis of the existing approaches indicates that they do not always adequately describe the experimental results. A qualitative model for describing the dependence of a crystalline substance heat capacity on temperature at a constant volume is proposed in this paper. The model describes the change in the number of particles of a new phase of a crystalline substance at a constant volume and is based on Einstein principle of detailed balance. An expression for metal heat capacity adequately corresponded to Dulong-Petit heat capacity is obtained. A model for describing the dependence of heat capacity on temperature in case of phase transitions is proposed. Розглянуто різні підходи до опису фазових переходів у кристалічних середовищах: феноменологічний підхід Ландау до опису фазових переходів другого роду, а також теорії кристалізації Колмогорова, Аврамі та Крістіана. Аналіз існуючих підходів показує, що вони не завжди адекватно описують експериментальні результати. У роботі запропонована якісна модель для опису залежності теплоємності кристалічної речовини від температури. Модель описує зміну кількості частинок нової фази кристалічної речовини при постійному об’ємі та заснована на принципі детальної рівноваги Ейнштейна. Отримано вираз для теплоємності металу, що адекватно відповідає теплоємності Дюлонга-Птi. Запропоновано модель для опису залежності теплоємності від температури в кристалічних середовищах. Рассмотрены различные подходы к описанию фазовых превращений в кристаллических средах: феноменологический подход Ландау к описанию фазовых переходов второго рода, а также теории кристаллизации Колмогорова, Аврами и Кристиана. Анализ существующих данных показывает, что они не всегда адекватно описывают экспериментальные результаты. В работе предложена качественная модель для описания зависимости теплоемкости кристаллической среды от температуры. Модель описывает изменение количества частиц новой фазы кристаллической среды при постоянном объеме и основана на принципе детального равновесия Эйнштейна. Получено выражение для теплоемкости металла, которое адекватно соответствует теплоемкости Дюлонга-Пти. Предложена модель для описания зависимости теплоемкости от температуры.